Genetic effects on serum testosterone and sex hormone-binding globulin in men: a Korean twin and family study - Sung, Joohon (Asian J Androl, 2016)
We conducted a community-based cross-sectional study to evaluate the role of genetics in determining the individual difference in total testosterone and sex hormone-binding globulin levels. Study participants comprised 730 Korean men consisting of 142 pairs of monozygotic twins, 191 pairs of siblings, and 259 father-offspring pairs from 270 families who participated in the Healthy Twin study. Serum concentration of total testosterone and sex hormone-binding globulin were measured by chemiluminescence immunoassay, and free testosterone and bioavailable testosterone were calculated using Vermeulen's method. Quantitative genetic analysis based on a variance decomposition model showed that the heritability of total testosterone, free testosterone, bioavailable testosterone, and sex hormone-binding globulin were 0.56, 0.45, 0.44, and 0.69, respectively after accounting for age and body mass index. Proportions of variance explained by age and body mass index varied across different traits, from 8% for total testosterone to 31% for sex hormone-binding globulin. Bivariate analysis showed a high degree of additive genetic correlation (ρ(G) = 0.67) and a moderate degree of individual-specific environmental correlation (ρ(E) = 0.42) between total testosterone and sex hormone-binding globulin. The findings confirmed the important role of genetics in determining the individually different levels of testosterone and sex hormone-binding globulin during adulthood in Korean men as found in non-Asian populations, which may suggest that common biologic control for determining testosterone level directly or indirectly through binding protein are largely shared among different populations.